SAT0242 Anakinra increases days of work and domestic activity in patients with rheumatoid arthritis. (1st June 2001) - Bresnihan, B; Chan, WW; Woolley, JM
Abstract : Background: Objectives: To evaluate the effect of anakinra treatment on days of work and domestic activity in patients with rheumatoid arthritis (RA). Methods: In a six-month, placebo-controlled study conducted in Europe, 473 patients with RA were randomised to receive anakinra 30, 75 or 150 mg/day or placebo. Days of work and domestic activity were evaluated at baseline and after 4, 8, 12, 16, 20, and 24 weeks of therapy using an economic resource survey. The total days of work and domestic activity gained after commencing treatment were quantified as productivity and compared in patients receiving placebo or anakinra. Results: Patients receiving anakinra demonstrated greater gains in productivity for all doses examined (see table). These gains occurred rapidly, with over a two-day gain by week 8, and over 13 days gained on completion of the study. Furthermore, at the end of the study, an additional 14% of patients receiving anakinra did not miss any work or domestic activity, compared to 6% receiving placebo (data not shown) Table 1 . Productivity (Work and Domestic Activity) Days Gained: Conclusion: Patients receiving anakinra treatment experienced rapid and dose-related increases in days of work and domestic activity.